A Scarcity of Gold? - Stuart, H. W. (Journal of Political Economy, 1895)
290 millions in I854, to 4I6 millions and finally in I857 to 448 millions. From I853-I857 France gained 1745 millions of gold. The movement of silver was of course exactly the reverse. Up to I852 it came in considerable quantities. In that year, however, the reaction set in. The excess of exportation for the year was 2.50 millions. In 1853 it was Ii6; in I854, I64; in 1855,I97; in i856, 284; in I857, 362 millions. During the last five years, France lost II 26 millions of silver, an annual average of 225 millions. Thus the law of I803 did not secure a " concurrent circulation". It furnished a circulation composed of the metal cheapest with reference to the ratio of 15'2 :i. FromI803-I848 this metal happened to be silver; from i848-1858 it happened to be gold. The transition from a silver to a gold medium of exchange was gladly welcomed by the French people who found the latter metal better suited than silver to the needs of their expanding commerce. " Despite the very profound change which had come about in the metallic circulation in consequence of the inflow of gold and the departure of silver, the public in general and commerce in especial did not manifest either anxiety for the present or apprehension for the future. They did not appear to suffer for they did not demand any remedy."" H. PARKER WILLIS.